Effect of several spaying methods on grazing heifer gains - Kuhl, Gerry L.; Goehring, T.; Ritter, B.; Laudert, S.; McCully, W. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Several spaying and ovarian autografting methods were tested in three field trials with 658 grazing heifers. None of the techniques examined were found to have a beneficial effect on heifer gains compared to intact controls. Heifers' initial weight, frame size, and body condition score were associated with cattle performance; however, their relative impact on gains varied across the three trials.
Keywords: Beef; Heifer; Performance; Spaying; Ovarian autografting